High-performance composite silica gel adsorption material and preparation method thereof
By preparing composite cellulose and introducing specific groups, a high-performance composite silica gel adsorption material is formed, which solves the problem of insufficient metal salt capacity of existing silica gel adsorption materials in adsorption water, and improves antibacterial performance, achieving more efficient wastewater treatment.
Patent Information
- Application Number
- CN202411392839.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-27
AI Technical Summary
Existing silicone adsorbent materials have insufficient ability to adsorb metal salts in water, and may lead to bacterial release during the desorption process, causing environmental pollution.
By preparing composite cellulose, epoxy groups, quaternary ammonium groups and morpholin groups are introduced, and the modified cellulose is grafted with glycidyl methacrylate and acrylamide to form a high-performance composite silica gel adsorption material to enhance the metal salt coordination ability and antibacterial properties.
The adsorption ability of silica gel adsorption materials to metal salts is significantly improved, and the antibacterial properties are maintained after repeated use, avoiding the fall of adsorption groups and antibacterial groups, and improving the effect of wastewater treatment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the field of silica gel adsorption materials, and in particular to a high-performance composite silica gel adsorption material and a preparation method thereof. Background Art
[0002] With the rapid development of urbanization and science and technology, the rapid development of natural resources and industrialization have generated a large amount of wastewater containing organic pollutants and inorganic ion pollutants and discharged into the environment, seriously damaging the soil, water environment and ecological environment. The adsorption method is widely used in wastewater treatment because of its simple operation, economical and efficient, good removal performance and other advantages.
[0003] The most important thing about the adsorption method is the selection of adsorption materials. Silica gel is a non-toxic amorphous substance with a porous structure. Due to its stable chemical structure, it is often used as an adsorption material. However, the adsorption capacity of silica gel is small and the selectivity is poor. It can no longer meet the current complex environment and needs. At the same time, since wastewater is often accompanied by a large number of bacteria, these bacteria are very likely to be released during the desorption process of the silica gel adsorption material, causing adverse effects. Summary of the invention
[0004] The purpose of the present invention is to provide a high-performance composite silica gel adsorption material and a preparation method thereof, which solves the problem that the existing silica gel adsorption material has insufficient ability to adsorb metal salts in water, and at the same time has a certain antibacterial ability.
[0005] The object of the present invention can be achieved by the following technical scheme: A method for preparing a high-performance composite silica gel adsorption material, comprising the following steps: Step S1: weighing the following raw materials in weight percentage: 2-3% composite cellulose, 30-35% sodium water glass and 2-3% urea, the balance being water; Step S2: mixing composite cellulose, sodium water glass, urea and water and ultrasonically dispersing them for 15-20 minutes to obtain a mixed solution, adjusting the pH value of the mixed solution to 10, pouring it into a mold, standing it at a temperature of 45° C. for 12-16 hours, washing it with water, and freeze-drying it to obtain a high-performance composite silica gel adsorption material; The composite cellulose is prepared by the following steps: Step A1: 5-bromosalicylaldehyde, morpholine and anhydrous ethanol are mixed, and under nitrogen protection, the stirring rate is 120-150 rpm, the temperature is 80°C, and paraformaldehyde is added, and the reaction is carried out for 24 hours to obtain intermediate 1; intermediate 1, N-ethylethylenediamine and methanol are mixed, and under nitrogen protection, the stirring rate is 120-150 rpm, and the temperature is 65°C, and the reaction is carried out for 12-14 hours to obtain intermediate 2; The ratio of 5-bromosalicylaldehyde, morpholine and paraformaldehyde is 0.025-0.03 mol: 0.025-0.03 mol: 1.2-1.4 g, and the ratio of intermediate 1 and N-ethylethylenediamine is 0.025-0.03 mol: 0.025-0.03 mol; During the reaction, under the action of paraformaldehyde, the ortho position of the hydroxyl group in 5-bromosalicylaldehyde is formylated, and the formyl group reacts with the secondary amine in morpholine to connect morpholine to 5-bromosalicylaldehyde to obtain intermediate 1. The aldehyde group in intermediate 1 reacts with the primary amine group in N-ethylethylenediamine to form an imine bond to obtain intermediate 2. Step A2: Mix microcrystalline cellulose, acetone and deionized water, stir and add benzoyl peroxide under nitrogen protection, at a stirring rate of 120-150 rpm and a temperature of 70° C., react for 10-15 minutes, then add glycidyl methacrylate and acrylamide, react for 8-10 hours, and obtain modified cellulose; The ratio of microcrystalline cellulose, acetone, deionized water, benzoyl peroxide, glycidyl methacrylate and acrylamide is 10-12 g: 70 mL: 80 mL: 0.85-0.9 g: 0.08-0.12 mol: 0.1-0.12 mol; During the reaction, under the action of the initiator benzoyl peroxide, microcrystalline cellulose undergoes graft copolymerization with double bonds in glycidyl methacrylate and acrylamide to obtain modified cellulose. Step A3: the modified cellulose and deionized water are mixed, stirred and a hydrochloric acid solution is added to adjust the pH value to 6, and a trimethylamine solution is added under stirring at a rate of 80-100 rpm and a temperature of 40° C., and the mixture is reacted for 6-8 hours, and then the intermediate 2 is added and the reaction is continued for 4-6 hours to obtain composite cellulose; The mass concentration of the hydrochloric acid solution is 5.5 g / L, the mass fraction of the trimethylamine solution is 30%, and the amount ratio of the modified cellulose, deionized water, trimethylamine solution and intermediate 2 is 5-5.5 g: 80-100 mL: 60-70 mL: 0.025-0.03 mol; During the reaction, under acidic conditions, the trimethylamine in the trimethylamine solution is quaternized, and then reacts with part of the epoxy groups in the modified cellulose to connect the quaternary ammonium groups to the modified cellulose, while another part of the epoxy groups reacts with the secondary amine in the intermediate 2 to obtain composite cellulose; The beneficial effects of the invention are as follows: the invention discloses a high-performance composite silica gel adsorption material and a preparation method thereof, which solves the problem that the existing silica gel adsorption material has insufficient ability to adsorb metal salts in water, and at the same time, the silica gel adsorption material also has certain antibacterial ability; microcrystalline cellulose is grafted and copolymerized with glycidyl methacrylate and acrylamide by an initiator to introduce epoxy groups, and the epoxy groups react with quaternized trimethylamine and intermediate 2 to obtain composite cellulose; the Schiff base structure in the composite cellulose can effectively coordinate with metal salts in wastewater to form a complex, thereby removing metal ions in water; and since morpholine groups are introduced into the composite cellulose, the morpholine groups can better promote the electrostatic attraction between ions after protonation, thereby improving the adsorption capacity of the silica gel adsorption material for metal salts; and quaternary ammonium groups are introduced by reacting with quaternized trimethylamine, and the introduction of quaternary ammonium groups greatly improves the antibacterial performance of the silica gel adsorption material, and since the composite cellulose is connected to the modified cellulose, the problem of performance degradation caused by the shedding of the adsorption groups or the shedding of the antibacterial groups after repeated use is avoided. DETAILED DESCRIPTION
[0006] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0007] Example 1 A method for preparing a high-performance composite silica gel adsorption material comprises the following steps: Step S1: weighing the following raw materials in weight percentage: 2% composite cellulose, 30% commercially available Narma sodium water glass and 2% urea, with the balance being water; Step S2: the composite cellulose, sodium water glass, urea and water are mixed and ultrasonically dispersed for 20 minutes to obtain a mixed solution, the pH value of the mixed solution is adjusted to 10, poured into a mold, and allowed to stand for 12 hours at a temperature of 45° C., washed with water, and freeze-dried to obtain a high-performance composite silica gel adsorption material; The composite cellulose is prepared by the following steps: Step A1: 5-bromosalicylaldehyde, morpholine and anhydrous ethanol were mixed, and under nitrogen protection, the stirring rate was 120 rpm, the temperature was 80°C, and paraformaldehyde was added for reaction for 24 hours to obtain intermediate 1; intermediate 1, N-ethylethylenediamine and methanol were mixed, and under nitrogen protection, the stirring rate was 120 rpm, the temperature was 65°C, and the reaction was carried out for 12 hours to obtain intermediate 2; The ratio of 5-bromosalicylaldehyde, morpholine and paraformaldehyde is 0.025 mol: 0.025 mol: 1.2 g, and the ratio of intermediate 1 and N-ethylethylenediamine is 0.025 mol: 0.025 mol; Step A2: Mix commercially available microcrystalline cellulose, acetone and deionized water, stir and add benzoyl peroxide under nitrogen protection, at a stirring rate of 120 rpm and a temperature of 70°C, and react for 10 minutes, then add glycidyl methacrylate and acrylamide, and react for 8 hours to obtain modified cellulose; The dosage ratio of microcrystalline cellulose, acetone, deionized water, benzoyl peroxide, glycidyl methacrylate and acrylamide is 10 g: 70 mL: 80 mL: 0.85 g: 0.08 mol: 0.1 mol; Step A3: the modified cellulose and deionized water were mixed, stirred and a hydrochloric acid solution was added to adjust the pH value to 6, and a trimethylamine solution was added under stirring at a rate of 80 rpm and a temperature of 40° C., and the mixture was reacted for 6 h, and then the intermediate 2 was added and the reaction was continued for 4 h to obtain a composite cellulose; The mass concentration of the hydrochloric acid solution is 5.5 g / L, the mass fraction of the trimethylamine solution is 30%, and the amount ratio of the modified cellulose, deionized water, trimethylamine solution and intermediate 2 is 5 g: 80 mL: 60 mL: 0.025 mol.
[0008] Example 2 A method for preparing a high-performance composite silica gel adsorption material comprises the following steps: Step S1: weigh the following raw materials in weight percentage: 3% composite cellulose, 35% commercially available Narma sodium water glass and 2% urea, the balance being water; Step S2: the composite cellulose, sodium water glass, urea and water are mixed and ultrasonically dispersed for 15 minutes to obtain a mixed solution, the pH value of the mixed solution is adjusted to 10, poured into a mold, and allowed to stand for 16 hours at a temperature of 45° C., washed with water, and freeze-dried to obtain a high-performance composite silica gel adsorption material; The composite cellulose is prepared by the following steps: Step A1: 5-bromosalicylaldehyde, morpholine and anhydrous ethanol were mixed, and under nitrogen protection, the stirring rate was 150 rpm, the temperature was 80°C, and paraformaldehyde was added for reaction for 24 hours to obtain intermediate 1; intermediate 1, N-ethylethylenediamine and methanol were mixed, and under nitrogen protection, the stirring rate was 150 rpm, and the temperature was 65°C, the reaction was carried out for 12 hours to obtain intermediate 2; The ratio of 5-bromosalicylaldehyde, morpholine and paraformaldehyde is 0.03 mol: 0.03 mol: 1.2 g, and the ratio of intermediate 1 and N-ethylethylenediamine is 0.025 mol: 0.03 mol; Step A2: Mix commercially available microcrystalline cellulose, acetone and deionized water, stir and add benzoyl peroxide under nitrogen protection, at a stirring rate of 120 rpm and a temperature of 70°C, and react for 15 minutes, then add glycidyl methacrylate and acrylamide, and react for 8 hours to obtain modified cellulose; The ratio of microcrystalline cellulose, acetone, deionized water, benzoyl peroxide, glycidyl methacrylate and acrylamide is 12 g: 70 mL: 80 mL: 0.85 g: 0.12 mol: 0.1 mol; Step A3: the modified cellulose and deionized water were mixed, stirred and a hydrochloric acid solution was added to adjust the pH value to 6, and a trimethylamine solution was added under stirring at a rate of 100 rpm and a temperature of 40° C., and the mixture was reacted for 8 h, and then the intermediate 2 was added and the reaction was continued for 4 h to obtain composite cellulose; The mass concentration of the hydrochloric acid solution is 5.5 g / L, the mass fraction of the trimethylamine solution is 30%, and the amount ratio of the modified cellulose, deionized water, trimethylamine solution and intermediate 2 is 5 g: 100 mL: 60 mL: 0.03 mol.
[0009] Example 3 A method for preparing a high-performance composite silica gel adsorption material comprises the following steps: Step S1: weigh the following raw materials in weight percentage: 3% composite cellulose, 35% commercially available Narma sodium water glass and 3% urea, and the balance is water; Step S2: the composite cellulose, sodium water glass, urea and water are mixed and ultrasonically dispersed for 20 minutes to obtain a mixed solution, the pH value of the mixed solution is adjusted to 10, poured into a mold, and allowed to stand for 16 hours at a temperature of 45° C., washed with water, and freeze-dried to obtain a high-performance composite silica gel adsorption material; The composite cellulose is prepared by the following steps: Step A1: 5-bromosalicylaldehyde, morpholine and anhydrous ethanol were mixed, and under nitrogen protection, the stirring rate was 150 rpm, the temperature was 80°C, and paraformaldehyde was added for reaction for 24 hours to obtain intermediate 1; intermediate 1, N-ethylethylenediamine and methanol were mixed, and under nitrogen protection, the stirring rate was 150 rpm, and the temperature was 65°C, the reaction was carried out for 14 hours to obtain intermediate 2; The ratio of 5-bromosalicylaldehyde, morpholine and paraformaldehyde is 0.03 mol: 0.03 mol: 1.4 g, and the ratio of intermediate 1 and N-ethylethylenediamine is 0.03 mol: 0.03 mol; Step A2: commercially available microcrystalline cellulose, acetone and deionized water were mixed, stirred at a stirring rate of 150 rpm and a temperature of 70°C under nitrogen protection, and benzoyl peroxide was added, reacted for 15 minutes, and then glycidyl methacrylate and acrylamide were added, and reacted for 10 hours to obtain modified cellulose; The ratio of microcrystalline cellulose, acetone, deionized water, benzoyl peroxide, glycidyl methacrylate and acrylamide is 12 g: 70 mL: 80 mL: 0.9 g: 0.12 mol: 0.12 mol; Step A3: the modified cellulose and deionized water were mixed, stirred and a hydrochloric acid solution was added to adjust the pH value to 6, and a trimethylamine solution was added under stirring at a rate of 100 rpm and a temperature of 40° C., and the mixture was reacted for 8 h, and then the intermediate 2 was added and the reaction was continued for 6 h to obtain composite cellulose; The mass concentration of the hydrochloric acid solution is 5.5 g / L, the mass fraction of the trimethylamine solution is 30%, and the amount ratio of modified cellulose, deionized water, trimethylamine solution and intermediate 2 is 5.5 g: 100 mL: 70 mL: 0.03 mol.
[0010] Comparative Example 1 Compared with Example 3, this comparative example is different in that the intermediate 1 in the preparation process of composite cellulose in Example 3 is replaced by 5-bromosalicylaldehyde, and the other steps are the same.
[0011] Comparative Example 2 Compared with Example 3, this comparative example removes the trimethylamine solution in the process of preparing the composite cellulose in Example 3, and adds the same weight of trimethylamine solution in the process of preparing the high-performance composite silica gel adsorption material, and the other steps are the same.
[0012] Take the high-performance composite silica gel adsorption materials prepared in Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, and prepare the high-performance composite silica gel adsorption materials into a sample with a mass of 0.5 g. The sample is immersed in a copper sulfate, copper chloride and copper nitrate solution with a copper ion concentration of 0.025 mol / L, and placed on a vibrating shaker. At room temperature and a rotation speed of 400 rpm, shake for 4 hours, determine the cation concentration, and calculate its ion removal rate. The antibacterial performance is tested by the flask oscillation method. The sample is immersed in a copper sulfate solution with a copper ion concentration of 0.025 mol / L. The sample was placed on a shaking table, shaken for 4 hours at room temperature and a speed of 400 rpm, dried, added to a sulfuric acid solution with a pH value of 1, continued to shake for 1 hour, dried, and then added to an ammonia solution with a pH value of 11, continued to shake for 2 hours, and dried. The above steps were used as a cycle step to repeat the adsorption and desorption process of the sample for 10 cycles, and then the copper ion removal rate was measured, and the copper ion removal rate retention rate was calculated. At the same time, the antibacterial performance after the cycle was tested, and the antibacterial performance retention rate was calculated. The test results are shown in Table 1: Table 1 Test results It can be seen from the test results in the table shown that when Example 1, Example 2 and Example 3 are compared with Comparative Example 1 and Comparative Example 2, Comparative Example 1 replaces the intermediate 1 in the preparation process of the composite cellulose in Example 3 with 5-bromosalicylaldehyde, and its adsorption performance is reduced due to the lack of morpholine groups. Comparative Example 2 removes the trimethylamine solution in the preparation process of the composite cellulose in Example 3, and adds the same weight of trimethylamine solution in the preparation process of the high-performance composite silica gel adsorption material. Due to the lack of chemical bond connection, its antibacterial performance after circulation is greatly reduced.
[0013] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0014] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-performance composite silica gel adsorption material, characterized in that: The method comprises the following steps: Step S1: weighing the following raw materials in weight percentage: 2-3% of composite cellulose, 30-35% of sodium water glass and 2-3% of urea, and the balance being water; Step S2: Mix composite cellulose, sodium water glass, urea and water and ultrasonically disperse for 15-20 minutes to obtain a mixed solution, adjust the pH value of the mixed solution to 10, pour it into a mold, let it stand for 12-16 hours at a temperature of 45°C, wash with water, and freeze-dry to obtain a high-performance composite silica gel adsorption material.
2. The method for preparing a high-performance composite silica gel adsorption material according to claim 1, characterized in that: The composite cellulose is prepared by the following steps: Step A1: 5-bromosalicylaldehyde, morpholine and anhydrous ethanol are mixed, and under nitrogen protection, the stirring rate is 120-150 rpm, the temperature is 80°C, and paraformaldehyde is added, and the reaction is carried out for 24 hours to obtain intermediate 1; intermediate 1, N-ethylethylenediamine and methanol are mixed, and under nitrogen protection, the stirring rate is 120-150 rpm, and the temperature is 65°C, and the reaction is carried out for 12-14 hours to obtain intermediate 2; Step A2: Mix microcrystalline cellulose, acetone and deionized water, stir and add benzoyl peroxide under nitrogen protection, at a stirring rate of 120-150 rpm and a temperature of 70° C., react for 10-15 minutes, then add glycidyl methacrylate and acrylamide, react for 8-10 hours, and obtain modified cellulose; Step A3: Mix the modified cellulose and deionized water, stir and add hydrochloric acid solution to adjust the pH value to 6, stir and add trimethylamine solution at a stirring rate of 80-100 rpm and a temperature of 40°C, react for 6-8 hours, then add intermediate 2 and continue to react for 4-6 hours to obtain composite cellulose.
3. The method for preparing a high-performance composite silica gel adsorption material according to claim 2, characterized in that: In step A1, the ratio of 5-bromosalicylaldehyde, morpholine and paraformaldehyde is 0.025-0.03 mol: 0.025-0.03 mol: 1.2-1.4 g, and the ratio of intermediate 1 and N-ethylethylenediamine is 0.025-0.03 mol: 0.025-0.03 mol.
4. The method for preparing a high-performance composite silica gel adsorption material according to claim 2, characterized in that: In step A2, the ratio of microcrystalline cellulose, acetone, deionized water, benzoyl peroxide, glycidyl methacrylate and acrylamide is 10-12 g: 70 mL: 80 mL: 0.85-0.9 g: 0.08-0.12 mol: 0.1-0.12 mol.
5. The method for preparing a high-performance composite silica gel adsorption material according to claim 2, characterized in that: In step A3: the mass concentration of the hydrochloric acid solution is 5.5 g / L, the mass fraction of the trimethylamine solution is 30%, and the amount ratio of the modified cellulose, deionized water, trimethylamine solution and intermediate 2 is 5-5.5 g: 80-100 mL: 60-70 mL: 0.025-0.03 mol.
6. A high-performance composite silica gel adsorption material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-5.
